2016
DOI: 10.1177/1045389x16633768
|View full text |Cite
|
Sign up to set email alerts
|

B19-phase transition and related tensile properties of Ti50Ni30Cu20 shape memory alloy doped with hydrogen

Abstract: The B19-phase transition and the related tensile properties of Ti50Ni30Cu20 shape memory alloys were investigated after hydrogen doping. The results revealed that the presence of hydrogen suppressed the B2–B19 transition by decreasing transformation enthalpies. Aging at room temperature lowered martensitic transformation temperature, which might have been associated with the variation of hydrogen contents and states. Ti50Ni30Cu20 shape memory alloys manifested high thermal cycling stability after the aging tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Furthermore, Zuo et al (2016) and Kireeva et al (2017) indicated that even the transformation temperatures would vary with respect to the hydrogen concentration. Besides, it was demonstrated that hydrogen would induce an expansion of the NiTi structure and would provoke residual martensite variants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zuo et al (2016) and Kireeva et al (2017) indicated that even the transformation temperatures would vary with respect to the hydrogen concentration. Besides, it was demonstrated that hydrogen would induce an expansion of the NiTi structure and would provoke residual martensite variants.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of differential scanning calorimetry have been performed onNiTi charged with hydrogen [9,10]. The forward transformation ismassively affected compared to the reverse transformation where the transformation temperatures are reduced as the hydrogen amount is increased.…”
Section: Introductionmentioning
confidence: 99%